Analisis Wacana Kritis Model Van Dijk Terhadap Berita “Ma Wara’a al-Hill fi al-Munadharat al-Intikhobiyyah fi Indunisiya” dari Laman Indonesiaalyoum.com - Ishak, Dina Mustika; Kholisin, Kholisin (Prosiding Konferensi Nasional Bahasa Arab, 2024)
The debate over the election of presidential and vice presidential candidates is currently a hot topic of discussion. This social phenomenon has attracted the attention of all people in Indonesia, especially since the election debate was characterized by the use of tricks by each pair of candidates. This research aims to analyze text structure, social cognition, and social context in online news entitled "Ma Wara'a al-Hill fi al-Munadharat al-Intikhobiyyah fi Indunisiya" published by indonesiaalyoum.com. The research data source comes from online mass media regarding the implementation of election debates in Indonesia. This research includes descriptive research with the type of literature study. Data collection techniques through documentation, listening and taking notes. Research data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this research found that the news had themes and topics about election debate tricks in Indonesia. The news has met the level of discourse analysis using Teun A. Van Dijk's model, namely: 1) macro structure; 2) superstructure; and 3) microstructure. Based on critical discourse analysis of online news on the indonesiaalyoum.com portal, it can be concluded that the information conveyed meets the level of critical analysis of Teun A. Van Dijk's model 1) text structure; 2) social cognition; and social context. This research has implications for the entire community to be more aware of the importance of political education for Indonesia's more advanced future.